Development and Validation of a HPLC-MS/MS Method to Measure Nifuroxazide and Its Application in Healthy and Glioblastoma-Bearing Mice - Tommaso Ceruti; Quintino Giorgio D'Alessandris; Roberta Frapolli; Jay Gopalakrishnan; Mariachiara Buccarelli; Marina Meroni; Liverana Lauretti; Lucia Ricci-Vitiani; Roberto Pallini; Massimo Zucchetti (MDPI AG, 2022)
Nifuroxazide (NAZ), a nitrofuran derivative used to treat diarrhea, has been recently shown to possess anticancer activity. However, its pharmacokinetic profile is poorly known. The pharmacokinetic profile of NAZ was thus investigated in mice using a newly developed method based on high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). We determined the concentrations of NAZ in the plasma and brain tissue of mice treated with the drug. The method proved to be specific, reproducible, precise, and accurate. It also demonstrated high sensitivity, reaching an LOQ in the order of ppb for both matrices, using samples of 100 µL or 0.2 g. The new HPLC-MS/MS assay was successfully applied to study the pharmacokinetics of NAZ after chronic intraperitoneal administration in mice at a dose of 30 mg/kg. One hour after treatment, plasma concentrations of NAZ were in the range of 336-2640 ng/mL. Moreover, unlike the brains of healthy mice or those with healed mechanical injuries, we found that NAZ was able to cross the injured blood-brain barrier of tumor-infiltrated brains. Thus, following i.p. administration, NAZ reaches systemic levels suitable for testing its efficacy in preclinical models of glioblastoma. Overall, these pharmacokinetic data provide robust evidence supporting the repositioning of NAZ as an antitumor drug.